Multicenter evaluation of the supplementary therapeutic effect of porcine-derived lymphoreticular polypeptides in the clinical course of various pathologies - Acero Plazas, Víctor M.; Higuera Piedrahita, Rosa Isabel; Mejía Mejía, Guillermo (Spei Domus, 2020)
Introduction: The limpho-reticular polypeptides from porcine source has been postulated as an alternative immunomodulator agents in humans, and coadyuvants in treatment of cancer and other pathologies. The objective of this study was to cuantify the use of this peptides as a regular treatment and coadyuvants in several pathologies.Methods: One hundred and and thirty six (136) doctors in medicine and some others health professionals, previously qualified into a highly ethical and professional standards, placed in thirteen (13) Colombian cities, took part in a multicentrical, retrospective, valorative study , based in a Likert scale (Range1-9) that pretends to evaluate the “supplementary therapeutic effect” of some limpho-reticular polypeptides (Low Molecular Weight.-L.M.W.) developed in this country, observed during the clinical course of several pathologies, and alsoto know their attitude to allow for this innovative compounds in their regular medical practices.Results: A total of 6.510 patients were reported to be seen, and treated during a period of time, between the late six months and more than three years backward, based in clinical records. The results shown an interest in all segments and disciplines of medicine, for this organic compound and recognize them to be of utility in their current medical practices, despite of their holistic or reductive tendencies. Hundred per cent (100%) of the associate investigators valorate the supplementary therapeutic effects of this polypeptides, and reflex them into values between 7 and 9, meaning range (7) as good (33,8%), (8) in a range between good - and excellent (34,5%) , and 9 as excellent (26,4%), also reporting some outstanding cases.Conclusions: Based on the results, the use of these peptides as adjuvants in the treatment of various human pathologies is suggested.
Keywords: immunomodulators; lyophoreticular polypeptides; porcine; likert scale